Glucose exogenous increases biochemical and physiological responses in Beta vulgaris L. - João Vitor Melquiades da Silveira; Erich Cristian Pereira dos Santos; Lucas Pereira dos Santos; Carla Francisco de Freitas; Rodolfo Fioruci de Arruda; Robson Henrique Pedroso Garcia; Pedro Henrique Gorni (Advances in Horticultural Science)
Glucose can act as a bioregulator in plants, due to influencing physiological and metabolic processes. This investigation aimed to analyses how the application of glucose impacts the photosynthetic rate, growth, and concentration of bioactive compounds with antioxidant potential in beet. The current investigation evaluated the effect of glucose (0, 5, 10, 20, and 30 mmol L-1) on beet plants 10 days after transplantation. Glucose elicitation in beet plants increases levels of bioactive compounds, resulting in higher antioxidant potential. In addition to antioxidant benefits, glucose also plays a hormonal role, leading to increases in biomass. These effects are correlated with enhanced photosynthetic efficiency, elevated carbohydrate concentrations, and positive modulation of the plant antioxidant system.